The Anatomical Relationship Between the Hyoid Bone and the Carotid Arteries - Nektaria Karangeli; George Triantafyllou; Panagiotis Papadopoulos-Manolarakis; George Tsakotos; Katerina Vassiou; Marianna Vlychou; Panagiotis Papanagiotou; Maria Piagkou (Diagnostics, 2025)
Background: The anatomical relationship between the carotid arteries (CAs) and the hyoid bone (HB) has significant clinical implications. The present study investigates the spatial relationship between the HB and common carotid artery (CCA), internal carotid artery (ICA), external carotid artery (ECA), and carotid bifurcation (CB), analyzing their morphological variants and topographical associations. Materials and Methods: Computed tomography angiographies (CTAs) from 100 patients (50 males, 50 females; mean age 62.2 ± 14.5 years) were analyzed. Measurements included the HB greater horn length (GHL) and greater horn angle (GHA), CA distances, and classification of relationships of the CAs with the HB. Results: The mean GHL was 27.72 ± 3.91 mm, and the mean GHA was 110.36 ± 6.06 degrees. Males exhibited significantly longer GHs than females (p < 0.001). Suprahyoid bifurcations occurred in 35.5% of cases, with a mean CCA-GH distance of 4.54 ± 2.67 mm. Infrahyoid bifurcations were identified in 64.5% of cases, with mean ECA-GH and ICA-GH distances of 4.10 ± 3.11 mm and 6.72 ± 3.85 mm, respectively. GHL significantly influenced these distances. Type 6 (ECA positioned laterally to the GH) was the most prevalent carotid–hyoid configuration (18.5%). Conclusions: The present study provides essential insights into the topographical variability of the CAs relative to the HB, offering valuable guidance for surgical planning and vascular risk assessment. These findings are crucial for procedures such as carotid endarterectomy, where the proximity of the carotid arteries to the hyoid bone impacts the risk of vascular injury. Further research is warranted to explore the clinical implications of these anatomical relationships.